Pandan-flavored tea - Buenaventura, Almira A.; Azanza, Ma. Patricia V. (1998., 1998)
The general objective of this study was to develop a pandan-flavored tea. The first three phases of the study dealt with the incorporation and determination of the optimum levels of pandan extract to black, green, and oolong tea bases. The fourth phase involved the determination of the moisture and tannin contents of the most acceptable sample per tea base. The most acceptable level of pandan extract per tea base was determined through sensory evaluation using 24 panelists. The test concentrations of pandan extract incorporated into each of the tea bases were 50, 250, 200 ppm. The most acceptable pandan extract concentration was established for the oolong tea base. The amber-colored infusion of the 200 ppm pandan-flavored black tea sample was given a rating nearer the turbid description in line with turbid and clear as anchors. The ratings, however, of its pandan aroma and astringency were between the scale with none and strong as anchors while its tea aroma, bitterness and tea flavor ratings were nearer the strong anchors. The pandan flavor, on the other hand got a rating close to the none description of the same scale. However, there was no significant difference detected in the overall acceptability in all the black tea infusions. The 200 ppm flavored green tea sample had greenish yellow infusion which got a rating for clarity close to the turbid description of a scale with turbid and clear as anchors. Its tea aroma, bitterness, astringency and tea flavor had ratings near the strong anchor in a line scale with none and strong as anchors. On the other hand, the rating given to the pandan aroma of the 200 ppm pandan-flavored sample was almost the midpoint of the same scale while its pandan flavor was close to the none. No significant difference was detected in the overall acceptability in all the green tea infusions. The 150 ppm flavored green tea sample had light brownish-green infusion which got a rating for clarity near the middle of a scale with turbid and clear as anchors. Its tea aroma, bitterness, astringency and tea flavor also fell between a line scale with none and strong as anchors. On the other hand, the rating given to the pandan aroma and its flavor of the 150 ppm pandan-flavored sample fell close to none anchor of the same scale. The mean percent moisture of the most acceptable sample of black, green and oolong tea was 9.2, 8.4 and 9.4 respectively. On the other hand, the mean percent tannin contents of black, green and oolong tea was 0.044, 0.1300 and 0.0100 respectively.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Tea